Schottkyjeva bariera - Korošak, Dean (Vakuumist, 1998)
The description of the metal semiconductor contact in the framework of the general model incorporating the interfacial control layer between the metal and the ordered semiconductor is given. Special attention is given to the iCB Schottky structures for nonzero acceleration voltage featuring the disordered interfacial control layer characterized by the metal atoms incorporated into the semiconductor lattice and the DIGS continuum. The expression for the Schottky barrier height variation in ICB structures is given.
Keywords: površine; kovine; polprevodniki; tanke plasti